Effect of MgO/Al2O3 ratio on the crystallization behaviour of Li2O–MgO–Al2O3–SiO2 glass-ceramic and its wettability on Si3N4 ceramic. Issue 14 (15th July 2022) - Sun, Liangbo; Fang, Jian; Guo, Songsong; Shan, Tipeng; Wen, Yue; Liu, Chunfeng; Zhang, Jie
Abstract: The composition governs the crystallization ability, the type and content of crystal phases of glass-ceramics. Glass-ceramic joining materials have generated more research interest in recent years. Here, we prepared a novel Li2 O–MgO–Al2 O3 –SiO2 glass-ceramic for the application of joining Si3 N4 ceramics. We investigated the influence of the MgO/Al2 O3 composition ratio on microstructure and crystallization behaviour. The crystallization kinetics demonstrated that the glasses had excellent crystallization ability and high crystallinity. β-LiAlSi2 O6 and Mg2 SiO4 were precipitated from the glass-ceramics, and the increase of MgO concentration was conducive to the precipitation of Mg2 SiO4 . Among the glass-ceramic samples, the thermal expansion coefficient of LMAS2 glass-ceramic was 3.1 × 10 −6 /°C, which was very close to that of Si3 N4 ceramics. The wetting test showed that the final contact angle of the glass droplet on the Si3 N4 ceramic surface was 32° and the interface was well bonded.